A Polish saint. Historical-national themes in Franz Liszt’s oratorio ‘St Stanislaus’ - Golianek, Ryszard Daniel (Interdisciplinary Studies in Musicology, 2018)
Saint Stanislaus, a Polish bishop murdered in 1079 by King Boleslaus the Bold, is the title character of Franz Liszt’s oratorio St Stanislaus. The libretto of St Stanislaus has several authors - the first author was the Cracow man of letters and folklore scholar Lucjan Siemieński, whom Liszt asked to write a text for his oratorio. The libretto, completed in 1869, was translated by Peter Cornelius, who made certain changes to the order of events. Not until 1874 did Liszt set about writing the music for his oratorio in earnest, and that was when he asked Cornelius to revise the libretto. The author’s premature death thwarted that intention, and so Liszt was forced to seek other authors. The version prepared several years later by Karl Erdmann Edler finally met the composer’s expectations. In its final version, the libretto comprises four scenes, which form a logical sequence of events and at the same time serve to emphasise Stanislaus’ spiritual strength and the causative power of his actions. Liszt did riot succeed in setting the whole text of the libretto; the extant material covers only scenes 1 and 4. The musical style of St Stanislaus indicates that the composer drew on various types of musical inspiration and technique. Hence the work is characterised by a certain heterogeneity - a synthetic character that encapsulates a nineteenth-century aesthetics. Nevertheless, the oratorio is undoubtedly one of the most distinctive manifestations of Liszt’s interest in Polish subjects. The presence of quotations from the Polish songs ‘Boże, coś Polskę’ and ‘Jeszcze Polska nie zginęła’ lends the work a distinct national colouring and evokes a mood of solemnity and religious contemplation, as well as the aura of triumph, victory and domination. Such an attitude may be symptomatic of the typically nineteenth-century perception of Poland as a tormented nation deprived of its statehood, which thanks to its valour and resilience will ultimately regain its independence.